Explicitly accounting for needle sugar pool size crucial for predicting intra‐seasonal dynamics of needle carbohydrates δ18O and δ13C. Issue 6 (24th June 2022) - Leppä, Kersti; Tang, Yu; Ogée, Jérôme; Launiainen, Samuli; Kahmen, Ansgar; Kolari, Pasi; Sahlstedt, Elina; Saurer, Matthias; Schiestl‐Aalto, Pauliina; Rinne‐Garmston, Katja T.
Summary: We explore needle sugar isotopic compositions (δ 18 O and δ 13 C) in boreal Scots pine ( Pinus sylvestris ) over two growing seasons. A leaf‐level dynamic model driven by environmental conditions and based on current understanding of isotope fractionation processes was built to predict δ 18 O and δ 13 C of two hierarchical needle carbohydrate pools, accounting for the needle sugar pool size and the presence of an invariant pinitol pool. Model results agreed well with observed needle water δ 18 O, δ 18 O and δ 13 C of needle water‐soluble carbohydrates (sugars + pinitol), and needle sugar δ 13 C ( R 2 = 0.95, 0.84, 0.60, 0.73, respectively). Relative humidity (RH) and intercellular to ambient CO2 concentration ratio ( C i / C a ) were the dominant drivers of δ 18 O and δ 13 C variability, respectively. However, the variability of needle sugar δ 18 O and δ 13 C was reduced on diel and intra‐seasonal timescales, compared to predictions based on instantaneous RH and C i / C a, due to the large needle sugar pool, which caused the signal formation period to vary seasonally from 2 d to more than 5 d. Furthermore, accounting for a temperature‐sensitive biochemical 18 O‐fractionation factor and mesophyll resistance in 13 C‐discrimination were critical. Interpreting leaf‐level isotopic signals requires understanding on time integration caused by mixing in the needle sugar pool. Abstract : See also the Commentary on this article by Ubierna et al ., 236 : 2003–2008 .